Intermodal Freight Transport and Logistics - Monios, Jason (Taylor & Francis Group, 2017)
Ebookcentral.proquest; Applying sophisticated management techniques to freight transport offers the potential for significant cost savings as well as greater efficiency. Yet the inherent complexity of intermodal transport presents many challenges. This practical textbook on the operations of intermodal transport and logistics focuses on the practical concerns and the basics of operations, such as vehicles, containers, handling operations, logistics management and optimisation. All chapters are written by field specialists, and the volume includes additional chapters on economics, law and the environment to put the practical topics into context. It presents a balanced textbook for postgraduate students and also a reference text for those in industry or the public sector involved in the planning of intermodal freight transport.